Interview with Samantha King - Samantha King (Journal of Economic Sociology, 2022)
The interview with professor Samantha King, the author of the famous Pink Ribbons, Inc: Breast Cancer and the Politics of Philanthropy (Minneapolis: University of Minnesota Press, 2006), reveals her current studies within the field of cultural politics of health, sport and the body. Samantha introduces her research group in Queen’s University that critically looks at the healthification of market and political processes when social control, inequality and power asymmetry are pursued under the super value of health. She describes how her team uses the genealogical method by M. Foucault to reconstruct the dynamics of historical, ideological, economic, social agendas that shape local judgments about fruitful cultural frames for corporate charity, medicalized performance in professional sport, and painkiller use by people from different social classes. King’s Group studies criticize discourses about individual responsibility and good citizenship as those that may welcome getting pills into bodies instead of transforming the economic and social contexts out of which the disease arises. In the interview, Samantha traces the changes in anti-cancer philanthropy in recent years, comments on the political struggles behind the COVID-19 pandemic and points to the the hidden layers of the protein supplements market challenged by the post-humanistic ban on eating animals, emerging laboratory-meat supply, and ecological concern. The interview with Samantha King as well as her scientific articles will be useful for those who reflect on the incorporation of the human body and subjectivity into capitalistic production in different geopolitical realms.